Diamine, polymer and polyimide for liquid crystal aligning agent

By using a liquid crystal alignment agent containing a new diamine and a polymer with a specific structure in the liquid crystal display element, the problem of the difference in refractive index between the transparent conductive film and the liquid crystal alignment film is solved, and the effects of high refractive index, low reflection and high brightness are achieved.

CN119569593APending Publication Date: 2025-03-07NISSAN CHEM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411750590.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-09-24
Filing Date
2020-09-23
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the existing liquid crystal display elements, the difference in refractive index between the transparent conductive film and the liquid crystal orientation film leads to light reflection and reduces the display brightness, especially in high-fine panels.

Method used

By using a liquid crystal alignment agent containing a novel diamine and a polymer with a specific structure, a liquid crystal alignment film with a high refractive index and no colorability is formed, thereby reducing the refractive index difference with the transparent conductive film.

Benefits of technology

A liquid crystal alignment film with a high refractive index in a liquid crystal display element is realized, which reduces light reflection, improves display brightness, and maintains high light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569593A_ABST
    Figure CN119569593A_ABST
Patent Text Reader

Abstract

Provided are: a diamine, a polymer, and a polyimide for a liquid crystal aligning agent, which form a liquid crystal alignment film for vertical alignment (VA), said liquid crystal alignment film having a high refractive index and having a high light transmittance due to no colorability; a diamine represented by formula (2-1). A polymer is derived from a diamine component of the diamine. A polyimide which is a polyimide precursor obtained by polycondensation of a tetracarboxylic acid component and a diamine component including the diamine, or an imidized product of the polyimide precursor. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the following application:

[0002] Invention name: Liquid crystal alignment agent for vertical alignment, liquid crystal alignment film, and liquid crystal display element

[0003] International filing date: September 23, 2020

[0004] International application number: PCT / JP2020 / 035773

[0005] National application number: 202080066916.0 Technical Field

[0006] The present invention relates to a liquid crystal alignment agent for vertical alignment (VA); a liquid crystal alignment film obtained from the liquid crystal alignment agent; a liquid crystal display element having the liquid crystal alignment film; and novel diamines and polymers suitable for the liquid crystal alignment agent, the liquid crystal alignment film, and the liquid crystal display element. Background Art

[0007] Liquid crystal display elements are widely used in small applications such as mobile phones and smart phones, as well as larger applications such as televisions and monitors. Liquid crystal display elements are generally configured such that a pair of electrode substrates are arranged opposite to each other with a predetermined gap (several μm) therebetween, and liquid crystal is sealed between the electrode substrates. In addition, a voltage is applied between the transparent conductive films of the electrodes constituting the electrode substrates to perform display in the liquid crystal display element. These liquid crystal display elements have a liquid crystal alignment film that is indispensable for controlling the arrangement state of liquid crystal molecules.

[0008] On the other hand, various driving methods are being developed for liquid crystal display elements, which differ in electrode structure, physical properties of liquid crystal molecules used, etc. For example, various modes such as TN (Twisted Nematic) method, STN (Super Twisted Nematic) method, VA (Vertical Alignment) method, IPS (In-Plane Switching) method, and FFS (fringe field switching) method are known.

[0009] Among them, VA (vertical alignment) liquid crystal display elements have a wide viewing angle, fast response speed, and high contrast. In addition, they do not require brushing or grinding in the production process. Therefore, they are widely used, especially for large-scale televisions and monitors with high demand.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: International Publication No. 2008 / 117615

[0013] Patent Document 2: Japanese Patent Application Publication No. 2008-76950 Summary of the invention

[0014] Problems to be solved by the invention

[0015] Furthermore, the above-mentioned transparent conductive film in the liquid crystal display element is usually formed by a composition (ITO) composed of indium oxide as the main component and several percent of tin oxide doped therein, but its refractive index is different from that of the liquid crystal alignment film and has a high value. Therefore, when trying to make the light from the display light source pass through the electrode substrate, the light will be reflected at the boundary surface between the transparent conductive film and the liquid crystal alignment film in each electrode substrate. As a result, the transmittance of the electrode substrate cannot be fully obtained, resulting in the undesirable situation of reduced display brightness.

[0016] In particular, in recent years, ultra-high-definition panels such as 4K and 8K are being developed, but in these panels, the occupancy rate of the black matrix (BM), TFT, etc. increases, the aperture ratio of the panel decreases, and attention is paid to improving the transmittance of the display part.

[0017] Therefore, the inventors of the present invention have conducted various studies on the materials for forming the liquid crystal alignment film in order to improve the refractive index of the liquid crystal alignment film, considering that the above-mentioned undesirable situation can be eliminated by reducing the difference between the refractive index of the transparent conductive film and the refractive index of the liquid crystal alignment film. Specifically, the inventors have explored the types of polymers contained in the liquid crystal alignment agents for forming the liquid crystal alignment film in order to improve the refractive index of the liquid crystal alignment film.

[0018] As a result, it was found that a liquid crystal alignment film having a refractive index close to that of a transparent conductive film can be obtained by selecting a specific polymer, but on the other hand, when a large number of polymers are used to form a liquid crystal alignment film having a high refractive index, the liquid crystal alignment film has coloration. The liquid crystal alignment film formed by a liquid crystal alignment agent containing a polymer having coloration has a low light transmittance, resulting in a decrease in display brightness, and as a result, the above-mentioned purpose cannot be achieved.

[0019] The object of the present invention is to provide a liquid crystal orientation agent for forming a liquid crystal orientation film for VA (vertical orientation) having a high refractive index and high transmittance due to non-colorability, a liquid crystal orientation film obtained from the liquid crystal orientation agent, and a liquid crystal display element having the liquid crystal orientation film in view of the above situation.

[0020] Solutions for solving problems

[0021] The present inventors have conducted intensive studies to achieve the above-mentioned problems and, as a result, have found that a liquid crystal aligning agent containing a part of a novel polymer having a specific structure is effective for achieving the above-mentioned purpose, thereby completing the present invention.

[0022] The present invention relates to a liquid crystal alignment agent for vertical alignment (VA), a liquid crystal alignment film obtained from the liquid crystal alignment agent, and a liquid crystal display element having a vertical alignment mode of the liquid crystal alignment film, wherein the liquid crystal alignment agent is characterized in that it contains at least one polymer (P) selected from the group consisting of a polyimide precursor obtained by using a diamine component containing a diamine (0) represented by the following formula (0), and a polyimide which is an imide product of the polyimide precursor.

[0023] H2N-ALA′-NH2 (0)

[0024] (A and A' each independently represent a monocyclic group, a condensed ring group, or a group formed by bonding two monocyclic groups, and at least one of A and A' represents a condensed ring group. L represents a single bond or a -X1-Q-X2- group. X1 and X2 each independently represent a single bond, an oxygen atom, or a sulfur atom. Q represents an alkylene group having 1 or 2 carbon atoms.)

[0025] Effects of the Invention

[0026] According to the present invention, a liquid crystal alignment agent for vertical alignment (VA) can be obtained, which forms a liquid crystal alignment film having a high refractive index and having a high light transmittance due to lack of coloring. Since the liquid crystal alignment film formed by the liquid crystal alignment agent has a high refractive index, the difference between the refractive index of the transparent conductive film in the liquid crystal display element and the refractive index of the liquid crystal alignment film can be reduced. In addition, since it has no coloring, a liquid crystal display element of vertical alignment (VA) mode with high light transmittance and high display brightness can be obtained. DETAILED DESCRIPTION

[0027] As described above, the liquid crystal aligning agent of the present invention contains at least one polymer (P) selected from the group consisting of a polyimide precursor obtained using a diamine component containing a diamine (0) represented by the following formula (0) and a polyimide which is an imide product of the polyimide precursor.

[0028] H2N-ALA'-NH2 (0) In the above formula (0), A, A', L, X1 and X2 are as defined above.

[0029] The monocyclic group in A and A' refers to a divalent group formed by removing two hydrogen atoms from a monocyclic ring. Examples of the monocyclic ring include benzene; five-membered heterocyclic rings such as furan, thiophene, pyrrole, oxazole, thiazole, imidazole, and pyrazole; and six-membered heterocyclic rings such as pyran, pyrone, pyridine, pyridazine, pyrimidine, and pyrazine. The monocyclic ring is preferably benzene or pyridine. It should be noted that when the monocyclic ring is benzene, the monocyclic group is phenylene.

[0030] The condensed ring group in A and A' refers to a divalent group formed by removing two hydrogen atoms from a condensed ring. Examples of the condensed ring include condensed polycyclic aromatic hydrocarbons such as naphthalene, tetralin, indene, fluorene, anthracene, phenanthrene, and pyrene; and condensed polycyclic heterocyclic rings such as benzofuran, thionaphthene, indole, carbazole, coumarin, benzopyrone, quinoline, isoquinoline, acridine, phthalazine, quinazoline, and quinoxaline. The condensed ring is preferably naphthalene, anthracene, pyrene, indole, carbazole, coumarin, benzopyrone, quinoline, or isoquinoline.

[0031] The group formed by bonding two monocyclic groups is preferably a biphenyl structure or a bipyridyl group.

[0032] Among them, from the viewpoint of obtaining the effects of the present invention, A and A′ are preferably a phenylene group, a pyridyl group, a naphthylene group, an anthracenyl group, a quinolyl group, a biphenyl structure, or a bipyridyl group.

[0033] L is preferably a single bond, -O-(CH2) n -(n is an integer of 1 or 2), or -O-(CH2) n -O-(n is an integer 1 or 2).

[0034] Specific examples of the diamine (0) represented by the above formula (0) include the following formulas (d-1) to (d-21).

[0035]

[0036]

[0037] Preferred specific examples of the diamine (0) represented by the above formula (0) include diamines represented by the following formula (1).

[0038]

[0039] In the above formula (1), A, L, X1, and X2 are as defined above.

[0040] Preferred specific examples of the diamine (1) represented by the above formula (1) include formulas (d-1) to (d-7), (d-13) to (d-14), (d-17) to (d-18), and (d-21) in the above formulas (d-1) to (d-21).

[0041] The polymer (P) contained in the liquid crystal alignment agent of the present invention is preferably at least one polymer selected from the group consisting of a polyimide precursor obtained by using a diamine component containing a diamine (s), and a polyimide that is an imide product of the polyimide precursor, in addition to the diamine represented by the above formula (0), wherein the diamine (s) has at least one polymer selected from the group consisting of structures represented by the following formulas (S1) to (S3).

[0042]

[0043] In formula (S1), X 1 and X 2 Each independently represents a single bond, -(CH2) a -(a is an integer of 1 to 15), -CONH-, -NHCO-, -CON(CH3)-, -NH-, -O-, -COO-, -OCO- or -((CH2) a1 -A1) m1 -(a1 is an integer of 1 to 15, A1 represents an oxygen atom or -COO-, and m1 is an integer of 1 to 2. When m1 is 2, a plurality of a1s and A1s each independently have the above definition). 1 and G 2 Each independently represents a divalent cyclic group selected from a divalent aromatic group having 6 to 12 carbon atoms and a divalent alicyclic group having 3 to 8 carbon atoms. Any hydrogen atom on the cyclic group is optionally substituted by an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorinated alkyl group having 1 to 3 carbon atoms, a fluorinated alkoxy group having 1 to 3 carbon atoms, or a fluorine atom. m and n are each independently an integer of 0 to 3, and the total of m and n is 1 to 6, preferably 1 to 4. R 1 represents an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms, forming R 1 Any hydrogen atom of is optionally substituted by a fluorine atom.

[0044] In addition, as G 1 , G 2 The divalent cyclic group in the formula (a) includes, for example, cyclopropylene, cyclohexylene, and phenylene. Any hydrogen atom on these cyclic groups may be substituted with an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorinated alkyl group having 1 to 3 carbon atoms, a fluorinated alkoxy group having 1 to 3 carbon atoms, or a fluorine atom.

[0045] -X 3 -R 2 (S2)

[0046] In formula (S2), X 3R represents a single bond, -CONH-, -NHCO-, -CON(CH3)-, -NH-, -O-, -CH2O-, -COO- or -OCO-. 2 represents an alkyl group having 1 to 20 carbon atoms or an alkoxyalkyl group having 2 to 20 carbon atoms, forming R 2 Any hydrogen atom of is optionally substituted by a fluorine atom.

[0047] In addition, from the viewpoint of improving the liquid crystal orientation, R 2 An alkyl group having 3 to 20 carbon atoms or an alkoxyalkyl group having 2 to 20 carbon atoms is preferred.

[0048] -X 4 -R 3 (S3)

[0049] In formula (S3), X 4 Represents -CONH-, -NHCO-, -O-, -CH2O-, -OCH2-, -COO- or -OCO-. 3 Indicates a structure having a steroidal skeleton. 3 A structure containing a cholesteryl group, a cholesterol group or a lanostanyl group is preferred.

[0050] Preferred specific examples of the formula (S1) include the following formulas [S1-x1] to [S1-x7].

[0051]

[0052] In the above formula, R 1 X is an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms. p For -(CH2) a -(a is an integer of 1 to 15), -CONH-, -NHCO-, -CON(CH3)-, -NH-, -O-, -CH2O-, -CH2OCO-, -COO-, or -OCO-. A1 is an oxygen atom or -COO-* (wherein the bond with "*" is the bond with (CH2) a2 bonding), A2 is an oxygen atom *-COO- (wherein the bonding with "*" is bonded to (CH2) a2 bond), a3 is 0 or 1, a1 and a2 are each independently an integer of 1 to 10, and Cy is 1,4-cyclohexylene or 1,4-phenylene.

[0053] As a preferred specific example of formula (S2), X 3 is any of -O-, -CH2O-, -COO- or -OCO-, preferably R 2In the case of an alkyl group having 3 to 20 carbon atoms or an alkoxyalkyl group having 2 to 20 carbon atoms, R 2 In the case of an alkyl group having 3 to 20 carbon atoms, R 2 Any hydrogen atom of is optionally substituted by a fluorine atom.

[0054] As a preferred specific example of the above formula (S3), the following formula [S3-x] can be cited. It should be noted that in the formula [S3-x], X is the formula [X1], the formula [X2] or the formula [X3], Col is the formula [Col1], the formula [Col2] or the formula [Col3], and G is the formula [G1], the formula [G2], the formula [G3] or the formula [G4]. Me represents a methyl group.

[0055]

[0056] Preferred examples of the diamine (s) having structures represented by the above formulae (S1) to (S3) include diamines represented by the following formula (d1) or (d2).

[0057]

[0058] In formula (d1) and (d2), Y represents a side chain structure represented by formula (S1) to (S3) above, and the two Ys in formula (d2) may be the same or different. In addition, X represents a single bond, -O-, -C(CH3)2-, -NH-, -CO-, -(CH2) m -, -SO2-, -O-(CH2) m -O-, -O-C(CH3)2-, -CO-(CH2) m -, -NH-(CH2) m -、-SO2-(CH2) m -、-CONH-(CH2) m -、-CONH-(CH2) m -NHCO-, -COO-(CH2) m -OCO-, -COO-, -CONH-, -NH-(CH2) m -NH-, -SO2-(CH2) m -SO2-. m is an integer from 1 to 8.

[0059] Preferred specific examples of the diamine of the above formula (d1) include the following formulas (d1-1) to (d1-18).

[0060]

[0061] (n is an integer from 1 to 20.)

[0062]

[0063] As the diamine represented by the above formula (d2), there can be mentioned structures selected from the group consisting of the following formulae (d2-1) to (d2-6).

[0064]

[0065] In the above formula, X p1 ~X p8 Each independently corresponds to X in the above formulas [S1-x1] to [S1-x6] p Synonymous, X s1 ~X s4 Each independently represents -O-, -CH2O-, -OCH2-, -COO- or -OCO-, X a ~X f Indicates -O-, -NH-, -O-(CH2) m -O-, -C(CH3)2-, -CO-, -COO-, -CONH-, -(CH2) m -, -SO2-, -O-C(CH3)2-, -CO-(CH2) m -, -NH-(CH2) m -, -NH-(CH2) m -NH-, -SO2-(CH2) m -、-SO2-(CH2) m -SO2-, -CONH-(CH2) m -、-CONH-(CH2) m -NHCO-, or -COO-(CH2) m -OCO-,R 1a ~R 1h Each independently represents an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms. m is 1 to 8.

[0066] (Production of polymer (P))

[0067] The polymer (P) contained in the liquid crystal aligning agent of the present invention is a polyimide precursor obtained by using a diamine component containing the above-mentioned diamine (0), preferably a diamine component containing diamine (s) in addition to the above-mentioned diamine (0), or a polyimide as an imide product of the polyimide precursor. Here, the polyimide precursor is a polymer such as polyamic acid and polyamic acid ester that can obtain a polyimide by imidization.

[0068] The polyamic acid (P) as the polyimide precursor of the polymer (P) can be obtained by polymerization reaction of a diamine component containing the diamine (0), preferably a diamine component containing a diamine (s) in addition to the diamine (0), and a tetracarboxylic acid component.

[0069] In this case, the usage-amount of diamine (0) is preferably 1 to 100 mol %, more preferably 1 to 99 mol %, and further preferably 5 to 95 mol % based on the diamine component to be reacted with the tetracarboxylic acid component.

[0070] When using a diamine (s) in addition to the above diamine (0), the usage-amount of the diamine (s) is preferably 1 to 99 mol %, more preferably 1 to 95 mol % based on the diamine component to be reacted with the tetracarboxylic acid component.

[0071] The diamine component used in the production of the polyamic acid (P) may contain diamines other than diamine (0) and diamine (s) (hereinafter referred to as other diamines). Examples of other diamines are given below, but the present invention is not limited thereto.

[0072] p-phenylenediamine, m-phenylenediamine, 4-(2-(methylamino)ethyl)aniline, diamines having a carboxyl group such as 3,5-diaminobenzoic acid, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 1,2-bis(4-aminophenyl)ethane, 1,3-bis(4-aminophenyl)propane, 1,4-bis(4-aminophenyl)butane, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,2-bis(4-aminophenoxy)ethane, 1 , 2-bis(4-amino-2-methylphenoxy)ethane, 1,3-bis(4-aminophenoxy)propane, 1,4-bis(4-aminophenoxy)butane, 1,5-bis(4-aminophenoxy)pentane, 1,6-bis(4-aminophenoxy)hexane, 4-(2-(4-aminophenoxy)ethoxy)-3-fluoroaniline, bis(2-(4-aminophenoxy)ethyl)ether, 4-amino-4'-(2-(4-aminophenoxy)ethoxy)biphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 1,4-diaminonaphthalene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,7 diamines having a urea bond such as 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2'-bis(4-aminophenyl)propane, 1,3-bis(4-aminophenethyl)urea, diamines represented by the following formulas (a-1) to (a-6), preferably diamines having a photopolymerizable group at the end such as 2-(2,4-diaminophenoxy)ethyl methacrylate and 2,4-diamino-N,N-diallylaniline, diamines having a free radical initiating function such as the following formulas (R1) to (R5), 2,6-diaminopyridine, 3,4-diaminopyridine, 2,4-diaminopyrimidine diamines having a heterocyclic ring such as those of the following formulas (z-1) to (z-18), diamines having a diphenylamine skeleton such as those of the following formulas (Dp-1) to (Dp-3), diamines containing an organosiloxane such as 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, diamines having a group "-N(D)-" (D is a protective group which is detached by heating and replaced by a hydrogen atom, preferably a tert-butoxycarbonyl group) such as those of the following formulas (5-1) to (5-11), diamines having an oxazoline structure such as those of the following formulas (Ox-1) to (Ox-2), and diamines described in International Publication No. 2016 / 125870.

[0073]

[0074]

[0075] (d1 represents an integer from 2 to 10.)

[0076]

[0077] (n represents an integer from 2 to 10.)

[0078]

[0079] (Boc represents tert-butoxycarbonyl.)

[0080]

[0081] Among them, as other diamines, from the viewpoint of preferably obtaining the effect of the present invention, p-phenylenediamine, 3,5-diaminobenzoic acid, 4,4'-diaminodiphenylmethane, 4,4'-diaminobenzophenone, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2-(2,4-diaminophenoxy)ethyl methacrylate, 2,4-diamino-N,N-diallylaniline, diamines represented by the above formulae (R1) to (R5), diamines represented by the above formulae (z-1) to (z-18), diamines represented by the above formulae (5-1) to (5-11), and diamines represented by the above formulae (Ox-1) to (Ox-2) are preferred.

[0082] When other diamines are used in addition to the diamine (0), the amount of the other diamines used is preferably 1 to 99 mol %, more preferably 5 to 95 mol %, based on the total diamine components used.

[0083] When other diamines are used in addition to the diamine (0) and the diamine (s), the amount of the diamine (s) used is preferably 98 mol% or less, more preferably 94 mol% or less, based on the diamine component reacted with the tetracarboxylic acid component.

[0084] The usage-amount of the said other diamine is preferably 5-40 mol%, more preferably 10-40 mol%, based on the total diamine components used for manufacture of the polyamic acid (P).

[0085] For liquid crystal display elements using the PSA (Polymer Sustained Alignment) method and the SC-PVA (Patterned Vertical Alignment) mode, from the perspective of improving the response speed, when producing the polyamic acid (P), one or more of 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, a diamine having a photopolymerizable group at the end, a diamine represented by the above formula (R1) to (R5), and a diamine represented by the above formula (z-1) to (z-18) can be used, and the amount used is preferably 1 to 40 mol%, more preferably 5 to 40 mol%, relative to the total diamine components used in the production of the polyamic acid (P).

[0086] (Tetracarboxylic acid component)

[0087] When producing the polyamic acid (P), the tetracarboxylic acid component to be reacted with the diamine component is not limited to tetracarboxylic dianhydride but may be a derivative of tetracarboxylic dianhydride such as tetracarboxylic acid, a tetracarboxylic acid dihalide, a tetracarboxylic acid dialkyl ester, or a tetracarboxylic acid dialkyl ester dihalide.

[0088] The above-mentioned tetracarboxylic dianhydride or its derivatives can be listed as: aromatic tetracarboxylic dianhydride, aliphatic tetracarboxylic dianhydride or alicyclic tetracarboxylic dianhydride, or their derivatives. Here, the aromatic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups including at least one carboxyl group of an aromatic ring. The aliphatic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups bonded to a chain hydrocarbon structure. Among them, it is not necessary to be composed only of a chain hydrocarbon structure, and it can also have an alicyclic structure or an aromatic ring structure in part.

[0089] In addition, alicyclic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups including at least one carboxyl group bonded to an alicyclic structure. Among them, none of these four carboxyl groups is bonded to an aromatic ring. In addition, it is not necessary to be composed only of an alicyclic structure, and a chain hydrocarbon structure or an aromatic ring structure may also be present in a part thereof.

[0090] Among them, the tetracarboxylic dianhydride or a derivative thereof is preferably a substance represented by the following formula (T).

[0091]

[0092] In formula (T), X represents a structure selected from the group consisting of the following (x-1) to (x-13).

[0093]

[0094] In the above formula (x-1), R 1 ~R4 R each independently represents a hydrogen atom, a methyl group, an ethyl group, a propyl group, a chlorine atom or a phenyl group. 5 and R 6 Each independently represents a hydrogen atom or a methyl group. j and k each independently represent 0 or 1, A1 and A2 each independently represent a single bond, ether (-O-), carbonyl (-CO-), ester (-COO-), phenylene, sulfonyl (-SO2-) or amide (-CONH-), and two A2s may be the same or different. *1 is a bond to the anhydride group of one side, and *2 is a bond to the anhydride group of the other side.

[0095] Preferred specific examples of the above formulae (x-12) and (x-13) include the following formulae (x-14) to (x-29). * represents a bonding bond.

[0096]

[0097] Preferred specific examples of the tetracarboxylic dianhydride or its derivative represented by the above formula (T) include tetracarboxylic dianhydride or its derivative in which X is selected from the above formulae (x-1) to (x-7) and (x-11) to (x-13).

[0098] The ratio of tetracarboxylic dianhydride or its derivative represented by the above formula (T) to be used is preferably 1 mol% or more, more preferably 5 mol% or more, further preferably 10 mol% or more, based on 1 mol of all tetracarboxylic acid components used.

[0099] The tetracarboxylic dianhydride and its derivative used for the manufacture of the polyamic acid (P) may contain tetracarboxylic dianhydride or its derivative other than the said formula (T).

[0100] The polyamic acid (P) is obtained by reacting the diamine component and the tetracarboxylic acid component in a solvent (polycondensation). The solvent is not particularly limited as long as it dissolves the generated polymer.

[0101] Specific examples of the above-mentioned solvent include: N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, 1,3-dimethyl-2-imidazolidinone. In addition, when the polymer has high solvent solubility, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or the solvents represented by the following formulas [D-1] to [D-3] can be used.

[0102]

[0103] (In formula [D-1], D 1represents an alkyl group having 1 to 3 carbon atoms, wherein D 2 represents an alkyl group having 1 to 3 carbon atoms, wherein D 3 represents an alkyl group having 1 to 4 carbon atoms).

[0104] These solvents may be used alone or in combination. Furthermore, even if the solvent does not dissolve the polymer, it may be used in combination with the above-mentioned solvents within a range in which the generated polymer does not precipitate.

[0105] When the diamine component and the tetracarboxylic acid component are reacted in a solvent, the reaction can be carried out at any concentration, and the concentration of the diamine component and the tetracarboxylic acid component relative to the solvent is preferably 1 to 50% by mass, more preferably 5 to 30% by mass. The reaction can be carried out at a high concentration in the initial stage, and then the solvent can be added.

[0106] In the reaction, the total molar ratio of the diamine components to the tetracarboxylic acid components (total molar ratio of diamine components / total molar ratio of tetracarboxylic acid components) is preferably 0.8 to 1.2. As in a normal polycondensation reaction, the closer this molar ratio is to 1.0, the greater the molecular weight of the generated specific polymer.

[0107] The polyamic acid ester as a polyimide precursor can be obtained by, for example, a known method such as [I] a method of reacting a polyamic acid obtained by the above synthesis reaction with an esterifying agent, [II] a method of reacting a tetracarboxylic acid diester with a diamine, or [III] a method of reacting a tetracarboxylic acid diester dihalide with a diamine.

[0108] [Polyimide]

[0109] The polyimide contained in the liquid crystal aligning agent of the present invention is a polyimide obtained by ring-closing the above-mentioned polyimide precursor. In the polyimide, the ring-closure rate (also referred to as imidization rate) of the amic acid group does not necessarily need to be 100%, and can be arbitrarily adjusted according to the application and purpose.

[0110] As a method for imidizing a polyimide precursor to obtain a polyimide, there can be mentioned: thermal imidization in which a solution of a polyimide precursor is directly heated, or catalytic imidization in which a catalyst is added to a solution of a polyimide precursor. The temperature when the polyimide precursor is thermally imidized in a solution is 100 to 400° C., preferably 120 to 250° C., and it is preferably carried out while removing water generated by the imidization reaction to the outside of the system.

[0111] The catalytic imidization of the polyimide precursor is carried out as follows: a basic catalyst and an acid anhydride are added to a solution of the polyimide precursor, and stirred at -20 to 250°C, preferably at 0 to 180°C. The amount of the basic catalyst is 0.5 to 30 times the molar amount of the amic acid group, preferably 2 to 20 times the molar amount, and the amount of the acid anhydride is 1 to 50 times the molar amount of the amic acid group, preferably 3 to 30 times the molar amount. As a basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. can be listed, among which pyridine has a moderate alkalinity for the reaction to proceed, so it is preferred. As an acid anhydride, acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. can be listed, among which, if acetic anhydride is used, purification after the reaction is completed becomes easy, so it is preferred. The imidization rate based on the catalytic imidization can be controlled by adjusting the amount of catalyst, reaction temperature, and reaction time.

[0112] In the case of recovering the generated polyimide from the imidization reaction solution of the polyimide precursor, the reaction solution is put into a solvent to precipitate it. As the solvent used for precipitation, there can be listed: methanol, ethanol, isopropanol, acetone, hexane, butyl cellulose, heptane, methyl ethyl ketone, methyl isobutyl ketone, toluene, benzene, water, etc. After the polymer obtained by precipitating it by putting in the solvent is filtered and recovered, it can be dried at normal pressure or reduced pressure, at room temperature or by heating. In addition, when the polymer recovered by precipitation is redissolved in a solvent and the operation of reprecipitation and recovery is repeated 2 to 10 times, the impurities in the polymer can be reduced. As the solvent at this time, for example, alcohols, ketone hydrocarbons, etc. can be listed. When three or more solvents selected from them are used, the efficiency of purification is further improved, so it is preferred.

[0113] The polyimide precursor and the polyimide preferably have a polystyrene-converted weight average molecular weight (Mw) measured by gel permeation chromatography (GPC) of 1,000 to 500,000, and more preferably 2,000 to 300,000. In addition, the molecular weight distribution (Mw / Mn) represented by the ratio of Mw to the polystyrene-converted number average molecular weight (Mn) measured by GPC is preferably 15 or less, and more preferably 10 or less. Within this molecular weight range, good orientation of the liquid crystal display element can be ensured.

[0114] (Liquid Crystal Alignment Agent)

[0115] The liquid crystal aligning agent of the present invention is a liquid composition in which the polymer (P) and other components used as needed are preferably dispersed or dissolved in an appropriate solvent.

[0116] In the liquid crystal alignment agent of the present invention, for example, for the purpose of improving electrical properties, vertical alignment, solution properties, etc., in addition to the polymer (P), other polymers (hereinafter, also referred to as other polymers) may also be contained. As a specific example of other polymers, from the viewpoint of improving vertical alignment, in addition to the above-mentioned polymer (P), at least one polymer selected from the group consisting of a polyimide precursor obtained by using a diamine component containing the following diamine, and a polyimide as an imide product of the polyimide precursor may also be contained, wherein the diamine has at least one selected from the group consisting of the structures shown in the above-mentioned formulas (S1) to (S3).

[0117] The content ratio of other polymers is preferably 90 parts by mass or less, more preferably 10 to 90 parts by mass, further preferably 20 to 80 parts by mass, relative to 100 parts by mass of the total of the polymers contained in the liquid crystal aligning agent.

[0118] Other polymers are not particularly limited, and examples thereof include main skeletons such as polyimide precursors, polyimides, polysiloxanes, polyesters, polyamides, cellulose derivatives, polyacetals, polystyrene derivatives, poly(styrene-phenylmaleimide) derivatives, and poly(meth)acrylates. Among them, at least one selected from the group consisting of polyimide precursors, polyimides, polyamides, polyorganosiloxanes, poly(meth)acrylates, and polyesters is preferred. Among them, at least one selected from the group consisting of polyimide precursors, polyimides, and polysiloxanes is more preferred. It should be noted that other polymers may also be used in combination of two or more.

[0119] The liquid crystal alignment agent of the present invention may also contain other components other than the above as required. As such components, for example, at least one compound selected from the group consisting of a cross-linking compound having the following substituents and a cross-linking compound having a polymerizable unsaturated group, a functional silane compound, a metal chelating agent compound, a curing accelerator, a surfactant, an antioxidant, a sensitizer, a preservative, a compound for adjusting the dielectric constant and resistance of the liquid crystal alignment film, etc., wherein the substituent is selected from at least one of an epoxy group, an isocyanate group, an oxetane group, a cyclocarbonate group, a blocked isocyanate group, a hydroxyl group, and an alkoxy group.

[0120] Preferred specific examples of the crosslinking compound include compounds represented by the following formulae (CL-1) to (CL-11). Examples of the compound for adjusting the dielectric constant and resistance of the liquid crystal alignment film include monoamines having a nitrogen-containing aromatic heterocycle such as 3-aminomethylpyridine.

[0121]

[0122] Examples of the organic solvent used in the liquid crystal aligning agent of the present invention include N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-ethyl-2-pyrrolidone, N-(n-propyl)-2-pyrrolidone, N-isopropyl-2-pyrrolidone, N-(n-butyl)-2-pyrrolidone, N-(tert-butyl)-2-pyrrolidone, N-(n-pentyl)-2-pyrrolidone, N-methoxypropyl-2-pyrrolidone, N-ethoxyethyl-2-pyrrolidone, N-methoxybutyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropaneamide, 3-butoxy-N,N-dimethylpropaneamide, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2 -pentanone, ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, propyl 3-methoxypropionate, butyl 3-methoxypropionate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol n-propyl ether, ethylene glycol isopropyl ether, ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether, propylene glycol Monobutyl ether, propylene glycol diacetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether, dipropylene glycol dimethyl ether, diisobutyl carbinol (2,6-dimethyl-4-heptanol), diisobutyl ketone, isopentyl propionate, isopentyl isobutyrate, diisoamyl ether, ethylene carbonate, propylene carbonate, etc. These may be used in combination of two or more.

[0123] The solid content concentration in the liquid crystal aligning agent (the ratio of the total mass of the components other than the solvent of the liquid crystal aligning agent to the total mass of the liquid crystal aligning agent) is appropriately selected in consideration of viscosity, volatility, etc., and is preferably in the range of 1 to 10 mass%. From the perspective of forming a uniform and defect-free coating film, it is preferably 1 mass% or more, and from the perspective of the storage stability of the solution, it is preferably 10 mass% or less. The concentration of the polymer is particularly preferably 2 to 8 mass%.

[0124] <Liquid crystal alignment film>

[0125] The liquid crystal alignment film for vertical alignment using the liquid crystal alignment agent of the present invention can be manufactured in the following manner: the above-mentioned liquid crystal alignment agent is applied to a substrate, and the drying and firing processes are carried out in sequence. As the substrate used at this time, there is no particular limitation as long as it is a substrate with high transparency. In addition to using a glass substrate, a plastic substrate such as an acrylic substrate, a polycarbonate substrate, etc. can also be used. From the viewpoint of process simplification, it is preferred to use a substrate formed with an ITO electrode for liquid crystal drive, etc. In addition, in a reflective liquid crystal display element, if it is only a single-sided substrate, an opaque substrate such as a silicon wafer can also be used. As an electrode in this case, a material reflecting light such as aluminum can also be used.

[0126] Examples of the method for applying the liquid crystal alignment agent include screen printing, offset printing, flexographic printing, inkjet, dipping, roll coater, slit coating, spin coating, and spray coating. From the perspective of improving the production efficiency of the liquid crystal alignment film, a method of applying the liquid crystal alignment agent by flexographic printing or inkjet is preferred.

[0127] After the liquid crystal alignment agent is coated on the substrate, it is dried by a heating unit such as a heating plate, a thermal circulation oven, an IR (infrared) oven, etc., preferably at 40 to 150°C, depending on the solvent used in the liquid crystal alignment agent, and then preferably sintered at a temperature of 150 to 300°C, more preferably at 180 to 250°C, to form a liquid crystal alignment film.

[0128] If the thickness of the liquid crystal alignment film after baking is too thick, it is disadvantageous in the power consumption of the liquid crystal display element, and if it is too thin, the reliability of the liquid crystal display element may decrease. Therefore, it is preferably 5 to 300 nm, more preferably 10 to 100 nm.

[0129] <Liquid crystal display device>

[0130] The liquid crystal display element of this invention comprises the said liquid crystal aligning film.

[0131] In a VA-type liquid crystal display element, the coating film formed as described above may be used as a liquid crystal aligning film as it is, or may be subjected to a rubbing treatment or a PSA treatment described later, as necessary.

[0132] The liquid crystal alignment agent of the present invention is also preferably used for a liquid crystal display element manufactured by the following process: a liquid crystal layer is provided between a pair of substrates having electrodes, a liquid crystal composition containing a polymerizable compound polymerized by at least one of active energy rays and heat is arranged between the pair of substrates, a voltage is applied between the electrodes, and the polymerizable compound is polymerized by at least one of irradiation with active energy rays and heating. Here, the applied voltage can be set to, for example, a direct current or alternating current of 5 to 50 V. In addition, as active energy rays, ultraviolet rays are preferred. As ultraviolet rays, ultraviolet rays containing light with a wavelength of 300 to 400 nm are preferably ultraviolet rays containing light with a wavelength of 310 to 360 nm. As the irradiation amount of light, 0.1 to 20 J / cm 2 , more preferably 1 to 20 J / cm 2 .

[0133] As a method for manufacturing a liquid crystal display element using the liquid crystal alignment agent of the present invention, for example, the following method can be listed: the liquid crystal alignment agent is applied to a pair of substrates having a conductive film to form a coating film, the coating films are arranged opposite to each other with a layer of liquid crystal molecules therebetween to form a liquid crystal box, and the liquid crystal box is irradiated with light while a voltage is applied between the conductive films of the pair of substrates.

[0134] The above-mentioned liquid crystal display element controls the pre-tilt angle of the liquid crystal molecules through the PSA (Polymer Sustained Alignment) method. In the PSA method, a small amount of photopolymerizable compound, such as a photopolymerizable monomer, is mixed into the liquid crystal material in advance. After the liquid crystal box is assembled, the photopolymerizable compound is irradiated with ultraviolet rays or the like while a specified voltage is applied to the liquid crystal layer, and the pre-tilt angle of the liquid crystal molecules is controlled by the generated polymer. The orientation state of the liquid crystal molecules when the polymer is generated is also stored after the voltage is removed, so the pre-tilt angle of the liquid crystal molecules can be adjusted by controlling the electric field formed in the liquid crystal layer. In addition, in the PSA method, there is no need for brushing treatment, so it is suitable for the formation of a vertically oriented liquid crystal layer whose pre-tilt angle is difficult to control by brushing treatment.

[0135] The liquid crystal display element of the present invention is obtained by obtaining a substrate with a liquid crystal alignment film from the liquid crystal aligning agent of the present invention by the above-mentioned method, and then preparing a liquid crystal cell by a known method to produce a liquid crystal display element.

[0136] As a method for making a liquid crystal box, there can be given as an example: preparing a pair of substrates with liquid crystal orientation films formed thereon, scattering spacers on the liquid crystal orientation film of one substrate, bonding the other substrate with the liquid crystal orientation film surface facing inside, and sealing by injecting liquid crystal under reduced pressure; a method of sealing by bonding the substrates after dropping liquid crystal on the surface of the liquid crystal orientation film on which the spacers are scattered, etc.

[0137] Liquid crystals may also be mixed with polymerizable compounds that polymerize by ultraviolet irradiation or heat as described above. Examples of polymerizable compounds include compounds having one or more polymerizable unsaturated groups such as acrylate groups or methacrylate groups in the molecule, such as polymerizable compounds represented by the following formulas (M-1) to (M-3).

[0138]

[0139] At this time, the content of the polymerizable compound is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the liquid crystal component. If the polymerizable compound is less than 0.01 parts by mass, the polymerizable compound does not polymerize, and the orientation control of the liquid crystal cannot be performed. If the polymerizable compound is more than 10 parts by mass, the unreacted polymerizable compound becomes more, and the residual image characteristics of the liquid crystal display element are reduced. After the liquid crystal box is made, while applying an AC and DC voltage to the liquid crystal box, the polymerizable compound is polymerized by heat and ultraviolet irradiation. Thus, the orientation of the liquid crystal molecules can be controlled.

[0140] The liquid crystal alignment agent of the present invention can also be used in a liquid crystal display element manufactured by the following process, that is, it can also be used in the SC-PVA mode: a liquid crystal layer is provided between a pair of substrates having electrodes, a liquid crystal alignment film containing a polymerizable group polymerized by at least one of active energy rays and heat is arranged between the above pair of substrates, and a voltage is applied between the electrodes. Here, as the active energy ray, ultraviolet rays are preferred. As ultraviolet rays, including the preferred scheme, ultraviolet rays used in the above-mentioned PSA method are applied. In the case of polymerization by heating, the heating temperature is 40 to 120°C, preferably 60 to 80°C. In addition, ultraviolet rays and heating can also be performed simultaneously.

[0141] In order to obtain a liquid crystal alignment film containing a polymerizable group that is polymerized by at least one of active energy rays and heat, there can be cited a method of adding a compound containing the polymerizable group to a liquid crystal alignment agent, and a method of using a polymer component containing a polymerizable group. As a specific example of a polymer containing a polymerizable group, there can be cited a polymer obtained by using a diamine having a function of being polymerized by the above-mentioned light irradiation.

[0142] Example

[0143] The following examples are given to further illustrate the present invention, but the present invention is not limited to these examples. The abbreviations of the following compounds and the determination methods of each characteristic are as follows. In addition, unless otherwise specified, the numerical values ​​are mass references.

[0144] <Specific diamine>

[0145]

[0146] <Diamine(s)>

[0147]

[0148] <Other diamines>

[0149]

[0150] (Boc represents tert-butoxycarbonyl.)

[0151] (Tetracarboxylic dianhydride)

[0152]

[0153] (Organic Solvent)

[0154] NMP: N-methyl-2-pyrrolidone, BCS: butyl cellosolve.

[0155] THF: tetrahydrofuran.

[0156] [Viscosity]

[0157] The viscosity of the polyamic acid solution was measured at 25° C. using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample amount of 1.1 mL (milliliter) and a conical rotor TE-1 (1°34′, R24).

[0158] [Determination of molecular weight]

[0159] The molecular weights of the polyimide precursor and polyimide were measured as follows using a room temperature gel permeation chromatography (GPC) apparatus (GPC-101) (manufactured by Showa Denko K.K.) and columns (KD-803, KD-805) (manufactured by Shodex Corporation).

[0160] Column temperature: 50°C.

[0161] Eluent: N,N-dimethylformamide (as additives, lithium bromide monohydrate (LiBr·H2O) 30 mmol / L (liter), phosphoric acid / anhydrous crystals (o-phosphoric acid) 30 mmol / L, tetrahydrofuran (THF) 10 ml / L).

[0162] Flow rate: 1.0 ml / min.

[0163] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide (molecular weight: about 900,000, 150,000, 100,000 and 30,000) (manufactured by Tosoh Corporation) and polyethylene glycol (molecular weight: about 12,000, 4,000 and 1,000) (manufactured by Polymer Laboratory).

[0164] [Determination of Imidization Ratio]

[0165] Add polyimide powder (20 mg) to an NMR (nuclear magnetic resonance) sample tube (NMR standard sampling tube, φ5 (manufactured by Kusano Scientific Co., Ltd.)), add deuterated dimethyl sulfoxide (DMSO-d6, 0.05 mass% TMS (tetramethylsilane) mixture) (0.53 ml), and apply ultrasound to completely dissolve it. The solution was measured by 500 MHz proton NMR in an NMR measuring machine (JNW-ECA500) (manufactured by JEOL DATUM Co., Ltd.). The imidization rate was calculated as follows: the proton derived from the structure that did not change before and after imidization was determined as the reference proton, and the peak integral value of the proton derived from the NH group of the amic acid appearing near 9.5 to 10.0 ppm was used to calculate it using the following formula.

[0166] Imidization rate (%) = (1-α·x / y) × 100

[0167] In the above formula, x is the peak integral value of protons derived from NH groups of amic acid, y is the peak integral value of reference protons, and α is the ratio of the number of reference protons to protons of one NH group of amic acid in the case of polyamic acid (imidation ratio 0%).

[0168] <Synthesis Example of Compound [DA-n-2]>

[0169] Compound [DA-n-2] was synthesized according to the following scheme.

[0170]

[0171] (Synthesis of Compound [1])

[0172] 6-Bronaphthalene-2-ol (150 g, 672 mmol) was added to dimethylformamide (1050 g) and cooled under ice. Sodium hydride (60%, 29.6 g) was added in small amounts, stirred under ice for 1 hour, and then benzyl bromide (121 g) was added and stirred at room temperature for 1 hour. Furthermore, pure water (750 g) was added in small amounts under water cooling and stirred to precipitate crystals, which were filtered and washed with methanol (750 g) as a slurry, filtered, and dried to obtain compound [1] (yield: 207 g, yield: 98%, white crystals).

[0173] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 8.13 (d, 1H, J = 2.0Hz), 7.85 (d, 1H, J = 9.2Hz), 7.78 (d, 1H, J = 8.8Hz), 7.58 (dd, 1H, J =8.8Hz, 2.4Hz), 7.53-7.48(m, 3H), 7.44-7.40(m, 2H), 7.38-7.33(m, 1H), 7.30(dd, 1H, J=9.0Hz, 2.6Hz), 5.22(s, 2H).

[0174] (Synthesis of Compound [2])

[0175] Sodium tert-butoxide (82.6 g) and benzophenone imine (126 g) were added to tetrahydrofuran (1000 g), and the mixture was stirred at room temperature for 30 minutes. Compound [1] (207 g, 661 mmol), PD2(dba)3 (tris(dibenzylideneacetone)dipalladium(0), 3.03 g) and BINAP (2,2'-bis(diphenylphosphino)-1,1'-binaphthyl, 6.17 g) were added thereto, and the mixture was stirred at 65°C for 23 hours under a nitrogen atmosphere. After cooling to room temperature, 1% hydrochloric acid (1000 g) was added, and the mixture was stirred at room temperature for 15 minutes, and the aqueous layer was separated. Ethyl acetate (200 g), hexane (100 g) and 1% hydrochloric acid (500 g) were further added to the organic layer, and the separated aqueous layer was added thereto. Sodium hydroxide (80 g) was added under water cooling to make the mixture alkaline. The organic layer was separated, washed with a saturated sodium chloride aqueous solution, dried with sodium sulfate, filtered, and the filtrate was concentrated to obtain a crude product (154 g). Ethyl acetate (462 g) was added to the crude product and heated at 70°C to dissolve it, and then hexane (770 g) was added and cooled. Then, the product was filtered and the filtrate was dried to obtain compound [2] (yield: 124 g, yield: 74%, light brown crystals).

[0176] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 7.50-7.43 (m, 4H), 7.42-7.37 (m, 2H), 7.35-7.30 (m, 1H), 7.19 (d, 1H, J= 2.8Hz), 7.04 (dd, 1H, J=8.8Hz, 2.8Hz), 6.90 (dd, 1H, J=8.8Hz, 2.0Hz), 6.80 (d, 1H, J=2.0Hz), 5.13 (br, 4H).

[0177] (Synthesis of Compound [3])

[0178] Compound [2] (124 g, 497 mmol) and di-tert-butyl dicarbonate (130 g) were added to dichloromethane (1000 g) and stirred at room temperature for 20 hours. The reaction was not completed, so di-tert-butyl dicarbonate (10 g) was added and stirred at room temperature for another 20 hours. Saturated sodium bicarbonate aqueous solution (1 L) and dichloromethane (300 g) were added and separated. The organic layer was washed with pure water (450 mL) and saturated sodium chloride aqueous solution (300 mL) in sequence, dried with sodium sulfate, filtered, and the filtrate was concentrated to obtain a crude product (198 g). Ethyl acetate (600 g) was added to the crude product and heated at 70°C to dissolve it, and then hexane (1000 g) was added and cooled. Then, it was filtered and the filtrate was dried to obtain compound [3] (yield: 142 g, yield: 82%, white crystals).

[0179] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 9.46 (s, 1H), 8.02 (s, 1H), 7.69 (t, 2H, J=8.6Hz), 7.52-7.49 (m, 2H), 7.45 (dd, 1H) , J=9.0Hz, 2.2Hz), 7.43-7.39 (m, 2H), 7.37-7.32 (m, 2H), 7.17 (dd, 1H, J=9.0Hz, 2.6Hz), 5.18 (s, 2H), 1.50 (s, 9H).

[0180] (Synthesis of Compound [4])

[0181] Compound [3] (122 g, 349 mmol) and 5% palladium carbon (12.2 g) were added to ethanol (976 g), and stirred at 40° C. for 96 hours under a hydrogen atmosphere. The 5% palladium carbon was filtered and the filtrate was concentrated to obtain compound [4] (yield: 89.3 g, yield: 99%, white crystals).

[0182] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 9.52 (s, 1H), 9.37 (s, 1H), 7.94 (s, 1H), 7.62-7.59 (m, 1 H), 7.56 (d, 1H, J=9.2Hz), 7.39 (dd, 1H, J=9.0Hz, 2.2Hz), 7.04-7.00 (m, 2H), 1.50 (s, 9H).

[0183] (Synthesis of Compound [5])

[0184] 4-Nitrochlorobenzene (100 g, 635 mmol), ethylene glycol (551 g) and sodium hydroxide (23.1 g) were added to dimethyl sulfoxide (500 g) and heated at 100°C for 19 hours. After cooling to room temperature, ethyl acetate (560 g) and pure water (700 g) were added and separated. After recovering the upper layer, ethyl acetate (300 g) was added to the lower layer for separation, and the upper layers were combined. Pure water (400 g) and saturated sodium chloride aqueous solution (200 g) were added to the combined upper layers and separated again. The ethyl acetate layer was dried over sodium sulfate, filtered, and the filtrate was concentrated to obtain a crude product (110 g). Ethyl acetate (330 g) was added to the crude product and heated at 60°C to dissolve it, and hexane (550 g) was added and cooled. Then, it was filtered and the filtrate was dried to obtain compound [5] (yield: 64.2 g, yield: 55%, light yellow crystals).

[0185] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 8.21 (d, 2H, J=9.4Hz), 7.16 (d, 2H, J=9.4Hz), 4.97 (t, 1H, J=5.6Hz), 4.15 (t, 2H, J=4.8Hz), 3.77-3.73 (m, 2H).

[0186] (Synthesis of Compound [6])

[0187] Compound [5] (63.2 g, 345 mmol) was added to dichloromethane (1264 g) and cooled under ice. Triethylamine (52.4 g), p-toluenesulfonyl chloride (69.0 g) and 4-dimethylaminopyridine (1.26 g) were added thereto and stirred at room temperature for 19 hours. Pure water (632 g) was added and the dichloromethane layer was recovered by liquid separation. The dichloromethane layer was separated and washed with 1% hydrochloric acid (300 g), pure water (300 g) and saturated sodium chloride aqueous solution (300 g) in sequence, dried with anhydrous sodium sulfate, filtered and the filtrate was concentrated to obtain compound [6] (yield: 108 g, yield: 93%, white crystals).

[0188] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 8.18 (d, 2H, J = 9.2Hz), 7.80 (d, 2H, J = 8.6Hz), 7.47 (d, 2H, J=8.6Hz), 7.05 (d, 2H, J=9.2Hz), 4.40-4.37 (m, 2H), 4.35-4.31 (m, 2H), 2.41 (s, 3H).

[0189] (Synthesis of Compound [7])

[0190] Compound [4] (45.0 g, 174 mmol), compound [6] (61.5 g) and potassium carbonate (36.0 g) were added to dimethylformamide (360 g) and stirred at 80°C for 21 hours. After cooling to room temperature, pure water (720 g) was added to precipitate crystals. The filtrate was filtered, and the filtrate was slurry-washed with methanol (360 g), filtered, and the filtrate was dried to obtain compound [7] (yield: 67.2 g, yield: 91%, light yellow earth-colored crystals).

[0191] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 9.47 (s, 1H), 8.23 ​​(d, 2H, J = 9.2Hz), 8.02 (s, 1H), 7.72-7.69 (m, 2H), 7.46 (dd, 1H, J = 8.8Hz, 2.0H z), 7.31 (d, 1H, J = 2.4Hz), 7.24 (d, 2H, J = 9.2Hz), 7.14 (dd, 1H, J = 9.0Hz, 2.6Hz), 4.56-4.53 (m, 2H), 4.46-4.43 (m, 2H), 1.50 (s, 9H).

[0192] (Synthesis of Compound [8])

[0193] Compound [7] (73.1 g, 172 mmol) was added to chloroform (1096 g), and trifluoroacetic acid (98.1 g) was added while stirring under water cooling, and the mixture was stirred at 50°C for 19 hours. After cooling to room temperature, triethylamine (87.0 g) and pure water (1096 g) were added to precipitate crystals. The mixture was filtered, and the filtrate was slurry-washed with methanol (365 g), filtered, and the filtrate was dried to obtain a crude product (49.5 g). Dimethylformamide (124 g) was added to the crude product, and it was heated and dissolved at 80°C, and methanol (248 g) was added and cooled to precipitate crystals. The mixture was filtered, and the filtrate was dried to obtain compound [8] (yield: 47.3 g, yield: 85%, orange crystals).

[0194] 1H-NMR (400MHz, DMSO-D6, δ (ppm)): 8.23 ​​(d, 2H, J=9.2Hz), 7.51 (dd, 1H, J=8.8Hz, 2.4Hz), 7.45 (dd, 1H, J=8.8Hz, 2.4Hz), 7.24 (dd, 2H, J=9. 2Hz, 2.4Hz), 7.27 (s, 1H), 7.01 (d, 1H, J=9.2Hz), 6.91 (d, 1H, J=8.8Hz), 6.80 (s, 1H), 5.15 (br, 2H), 4.55-4.51 (m, 2H), 4.41-4.37 (m, 2H).

[0195] (Synthesis of Compound [DA-n-2])

[0196] Compound [8] (46.4 g, 143 mmol) and 5% palladium on carbon (4.6 g) were added to dimethylformamide (371 g), and stirred at 60°C for 19 hours under a hydrogen environment. Since the reaction hardly proceeded, the mixture was stirred at 60°C for 8 hours under a 0.4 MPa hydrogen environment in an autoclave. After nitrogen substitution, 5% palladium on carbon was filtered, and the filtrate was concentrated to a content of 80 g. Dimethylformamide (46 g) was added, and after heating and dissolving it at 90°C, methanol (210 g) was added and cooled to precipitate crystals. Then, it was filtered and the filtrate was dried to obtain compound [DA-n-2] (yield: 33.4 g, yield: 79%, pale purple crystals).

[0197] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 7.50 (d, 1H, J = 8.8Hz), 7.44 (d, 1H, J = 8.8Hz), 7.13 (d, 1H, J = 2.8Hz), 7.00 (dd, 1H, J = 8.8Hz, 2.8Hz), 6.90 (dd, 1H, J = 8.8Hz, 2.4Hz), 6.79 (d, 1H, J=2.4Hz), 6.71 (d, 2H, J=8.8Hz), 6.52 (d, 2H, J= 8.8Hz), 5.13(br, 2H), 4.63(br, 2H), 4.28-4.25(m, 2H), 4.20-4.17(m, 2H).

[0198] <Synthesis of compound [DA-n-3]>

[0199] Compound [DA-n-3] was synthesized according to the following scheme.

[0200]

[0201] (Synthesis of Compound [9])

[0202] 6-Bromo-2-naphthylamine (30.0 g, 135 mmol), tetrahydrofuran (450 g), (4-nitrophenyl)boric acid (27.2 g, 163 mmol), methanol (300 g), cesium carbonate (132 g, 405 mmol), and water (150 g) were placed in a four-necked flask and replaced with nitrogen. Tetrakis(triphenylphosphine)palladium(0) (3.12 g, 2.70 mmol) was added, replaced with nitrogen, and stirred at 55°C overnight. After the reaction was completed, the reaction solution was added to water (750 g) to precipitate crystals, and the crystals were filtered and recovered. Isopropyl alcohol (216 g) was added to the obtained crystals, and the mixture was heated and stirred at 65°C. Toluene (300 g) was added while cooling to room temperature to cause crystallization. The resulting product was filtered, the filter cake was washed with toluene and hexane, and the crystals were dried to obtain compound [9] (yield: 28.0 g, 106 mmol, yield 78%).

[0203] 1 H-NMR (500MHz, DMSO-D6, δ (ppm)): 8.30 (d, J = 8.5Hz, 2H), 8.13 (s, 1H), 8.03 (d, J = 8.6Hz, 2H), 7.72 (d, J=8.8Hz, 2H), 7.63 (d, J=8.7Hz, 1H), 7.00 (d, J=8.5Hz, 1H), 6.85 (s, 1H), 5.63 (s, 2H).

[0204] (Synthesis of Compound [DA-n-3])

[0205] N,N-dimethylformamide (224 g) was added to compound [9] (28.0 g, 106 mmol), and nitrogen substitution was performed. Then, 5% palladium carbon (water-containing product, 2.24 g) was added to replace nitrogen, and a hydrogen Tedlar bag was assembled and stirred overnight at room temperature. After the reaction was completed, palladium carbon was removed by a membrane filter, and the filtrate was added to water (248 g) to precipitate crystals. The crystals (wet) were recovered by filtration. Isopropanol (50 g) was added to the obtained crystals, and the mixture was heated and stirred at 55°C. Toluene (74 g) was added while cooling to room temperature to crystallize. The crystals (crystals A) were recovered by filtration. The filtrate was concentrated, and crystallized again using isopropanol (55°C)-toluene (room temperature). The crystals (crystals B) were recovered by filtration. The obtained crystals A and B were dried to obtain compound [DA-n-3]. (yield: 17.6 g, 75.1 mmol, yield 71%).

[0206] 1H-NMR (500MHz, DMSO-D6, δ (ppm)): 7.76 (s, 1H), 7.60 (d, J=8.7Hz, 1H), 7.53-7.49 (m, 2H), 7. 41 (d, J=8.2Hz, 2H), 6.92 (d, J=8.7Hz, 1H), 6.80 (s, 1H), 6.66 (d, J=8.2Hz, 2H), 5.25 (s, 4H).

[0207] <Synthesis Example of Compound [DA-n-9]>

[0208] Compound [DA-n-9] was synthesized according to the following scheme.

[0209]

[0210] (Synthesis of Compound [4])

[0211] Compound [4] which is a synthetic intermediate in [DA-n-2] was used.

[0212] (Synthesis of Compound

[10] )

[0213] Ethylene glycol ditoluene sulfonate (60.7 g, 164 mmol), compound [4] (89.3 g) and potassium carbonate (56.7 g) were added to dimethylformamide (607 g) and stirred at 80°C for 22 hours. After cooling to room temperature, pure water (1200 g) was added to precipitate crystals. Then, the filtrate was filtered, and the filtrate was slurry-washed with methanol (450 g), filtered, and the filtrate was dried to obtain a crude product (83.9 g). Dimethylformamide (839 g) was added to the crude product, and after heating and dissolving it at 90°C, methanol (839 g) was added and cooled to precipitate crystals. Then, the filtrate was filtered and dried to obtain compound

[10] (yield: 71.2 g, yield: 80%, orange crystals).

[0214] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 9.43 (s, 2H), 7.99 (br, 2H), 7.67 (d, 4H, J=8.8Hz), 7.43 (dd, 2H, J=8.8Hz, 2.4Hz), 7.28 (d, 2H, J=2.4Hz), 7.12 (dd, 2H, J=8.8Hz, 2.4Hz), 4.42 (s, 4H), 1.47 (s, 18H).

[0215] (Synthesis of Compound [DA-n-9])

[0216] Compound

[10] (71.2 g, 129 mmol) was added to chloroform (1143 g) and cooled under water cooling. Trifluoroacetic acid (160 g) was added thereto and stirred at 50°C for 24 hours. After cooling to room temperature, triethylamine (142 g) and pure water (1143 g) were added to precipitate crystals. Then, the filtrate was filtered, the filtrate was slurry-washed with methanol (400 g), filtered, and the filtrate was dried to obtain a crude product (37.5 g). Dimethylformamide (225 g) was added to the crude product, heated at 90°C to dissolve it, and methanol (225 g) was added and cooled to precipitate crystals. Filtered, the filtrate was dried to obtain compound DA-n-9 (yield: 33.5 g, yield: 75%, light reddish purple crystals).

[0217] 1 H-NMR (400MHz, DMSO-D6, δ (ppm)): 7.51 (d, 2H, J = 8.8Hz), 7.45 (d, 2H, J = 8.8Hz), 7.17 (d, 2H, J = 2.4Hz), 7.02 (dd, 2H, J=8.8Hz, 2.4Hz), 6.91 (dd, 2H, J=8.8Hz, 2.4Hz), 6.80 (d, 2H, J=2.4Hz), 5.14 (br, 4H), 4.37 (s, 4H).

[0218] <Synthesis Example of Compound [DA-n-10]>

[0219] Compound [DA-n-10] was synthesized according to the following scheme.

[0220]

[0221] (Synthesis of Compound

[11] )

[0222] N, N-dimethylformamide (216 g) and potassium carbonate (33 g, 239 mmol) were added to tert-butyl (5-hydroxy-1-naphthyl) carbamate (27.0 g, 104 mmol) and stirred at 80°C. Then, a solution of 1, 2-bis (4-methylbenzenesulfonate) -1, 2-ethylene glycol (18.0 g, 496 mmol) in N, N-dimethylformamide (162 g) was added dropwise using a dropping funnel, and the mixture was heated and stirred at 80°C overnight. After the reaction was completed, the reaction solution was poured into water (2268 g) to precipitate crystals. The mixed solution was filtered using a Buchner funnel to obtain sticky black purple crystals (93 g). N,N-dimethylformamide was added to the obtained crude product, heated at 80°C to dissolve, and crystallized from methanol while cooling to room temperature, followed by filtration and drying to obtain compound

[11] (yield: 28.0 g, 51.4 mmol, yield 67%).

[0223] 1 H-NMR (500MHz, DMSO-D6, δ (ppm)): 9.14 (s, 2H), 7.98 (d, J = 10.0Hz, 2H), 7.64 (d, J = 10.0Hz, 2H), 7.55 (d, J = 1 0.0Hz, 2H), 7.46 (t, J=7.5Hz, 2H), 7.39 (t, J=7.5Hz, 2H), 7.13 (d, J=10.0Hz, 2H), 4.65 (s, 4H), 1.49 (s, 18H).

[0224] (Synthesis of Compound [DA-n-10])

[0225] Compound

[11] (28.0 g, 51.4 mmol) was charged with chloroform (374 g) and potassium carbonate (33 g, 239 mmol) and stirred at 80°C. Then, trifluoroacetic acid (31.0 g, 313 mmol) was slowly added dropwise using a dropping funnel, and the mixture was heated and stirred at 50°C for 6 hours. As a result, gray crystals were precipitated in the reaction system. After cooling to 25°C, the reaction solution was poured into water (374 g) and filtered. Triethylamine and water were added to the obtained crystals and stirred to release the diamine from the trifluoroacetate. The crystals were filtered again, washed with methanol and then with hexane, and dried to obtain compound [DA-n-10] (yield: 9.30 g, 27.0 mmol, yield 86%).

[0226] 1 H-NMR (500MHz, DMSO-D6, δ (ppm)): 7.65 (d, J = 7.5Hz, 2H), 7.41 (d, J = 8.0Hz, 2H), 7.29 (t, J = 8.0Hz, 2H), 7.12 (t, J=8.0Hz, 2H), 7.00 (t, J=7.5Hz, 2H), 6.67 (d, J=7.5Hz, 2H), 5.62 (s, 4H), 4.56 (s, 4H).

[0227] <Synthesis of DA-v-7>

[0228] Compound [DA-v-7] was synthesized according to the following scheme. "MeO" represents a methoxy group.

[0229]

[0230] (Synthesis of Compound 3 (Mixture of 3a and 3b))

[0231] Magnesium (15.39 g, 63.3 mmol, 1.5 eq.) was added to a four-necked flask, and after vacuum drying for 1 hour in a vacuum pump, THF (100 g) was added using a syringe and stirred at room temperature. Then, a solution of compound 1 (100 g, 42.2 mmol) in THF (300 g) was slowly added dropwise at a rate of about stable reflux. Then, the reaction solution was cooled to 0°C, and a solution of compound 2 (105.60 g, 42.2 mmol, 1.0 eq.) in THF (200 g) was added dropwise. After the addition was completed, the temperature of the reaction solution was returned to room temperature, and stirring was carried out at room temperature for 3 hours. Then, toluene (1 L) was added to dilute the reaction solution, and the reaction solution was cooled to 0°C again, and 10% acetic acid solution (500 g) was slowly added dropwise.

[0232] Next, the water layer was removed by liquid separation, and the organic layer was washed with saturated saline (1 L), saturated sodium bicarbonate aqueous solution (1 L), and saturated saline (1 L), and the organic layer was dried with anhydrous magnesium sulfate. Then, the mixture was filtered and distilled off using an evaporator to obtain crude crystals (172 g) of compound 3. The obtained crude crystals were directly used in the following reaction.

[0233] (Synthesis of Compound 4)

[0234] A mixture of crude crystals of compound 3 (172 g, 422 mmol), p-toluenesulfonic acid monohydrate (4.82 g, and 25.3 mmol, 0.06 eq.) in dehydrated toluene (MS4A dehydrated product, 2 L) was reacted for 2 hours under reflux while removing water. After the reaction was completed, about half of the toluene used was distilled off in an evaporator, and the solution was stirred at room temperature to precipitate solids. The obtained solids were filtered to obtain crystals of compound 4 (yield 150 g, yield 91%).

[0235] (Synthesis of Compound 5 (5a, 5b mixture))

[0236] A mixture of compound 4 (108 g, 276 mmol), 5% palladium carbon (water-containing product, 11 g, 10 wt%), ethyl acetate (1 L), and ethanol (1 L) was stirred at room temperature in the presence of hydrogen. After the reaction was completed, toluene (2 L) was added to dissolve the crystals, and the reaction mixture was filtered using celite, and the celite was washed with 1 L of toluene. The filtrate was concentrated under reduced pressure, and as a result, the target compound 5 (yield 103.3 g, yield 95%) was obtained.

[0237] (Synthesis of Compound 6)

[0238] At 0°C, under nitrogen substitution, BBr3 (1.0M-CH2Cl2, 243mL, 1.01mol) was added dropwise to a dichloromethane (800mL) solution of compound 5 (95.4g, 243mmol). After the addition, stir at 0°C for 2 hours. After the reaction is completed, add a small amount of the reaction solution to distilled water each time. Extract with ethyl acetate (1L), and wash the extract twice with 500mL of distilled water. After drying the organic layer with magnesium sulfate, the solvent was distilled off under reduced pressure. The obtained crude product was recrystallized in ethanol, filtered, and washed with ethanol. As a result, the target compound 6 (yield 18.6g, yield 21%) was obtained.

[0239] (Synthesis of Compound 8)

[0240] To a mixture of compound 6 (10.0 g, 26.4 mmol), potassium carbonate (11.0 g, 79.2 mmol, 3 eq.), and toluene (50 g), a toluene (20 g) solution of compound 7 (5.35 g, 26.4 mmol) was added dropwise under reflux. After the addition, the mixture was stirred overnight under reflux. After the reaction was completed, the reaction solution was cooled to about 60°C, ethyl acetate (500 g) was added, and the mixture was washed three times with distilled water. After the organic layer was dried with anhydrous magnesium sulfate, the solvent was distilled off under reduced pressure. The obtained crude product was recrystallized in an acetonitrile / ethanol (2:1) solution, filtered, and the filtered crystals were washed with ethanol to obtain crude crystals of compound 8. The crude crystals were purified by column chromatography (SiO2, CHCl3) to obtain crystals of compound 8 (yield 7.1 g, yield 49%).

[0241] (Synthesis of DA-v-7)

[0242] A mixture of compound 8 (12.2 g, 22.4 mmol), 5% palladium carbon (water-containing product, 1.22 g, 10 wt%), and 1,4-dioxane (120 g) was stirred at 60°C for 4 hours in the presence of hydrogen. After the reaction was completed, nitrogen substitution was performed and the mixture was filtered using diatomaceous earth while maintaining the temperature at 60°C. The filtrate was distilled under reduced pressure to remove the solvent, and as a result, a crude product was obtained. The crude product was recrystallized from 2-propanol / ethyl acetate (2:1) to obtain the target DA-v-7 (yield 8.0 g, yield 74%).

[0243] 1H-NMR (500MHz, CDCl3, δ (ppm)): 7.725 (1H, d), 7.577 (2H, m), 7.272 (2H, m), 7.102 (1H, s), 6.79 1(1H, d), 6.207(1H, d), 6.117(1H, dd), 3.621(4H, broad), 2.553(1H, m), 2.067-0.863(31H, m).

[0244] [Synthesis of polyamic acid]

[0245] <Synthesis example 1>

[0246] DA-4 (1.66 g, 7.00 mmol), DA-5 (2.89 g, 8.75 mmol), DA-v-6 (5.30 g, 7.00 mmol), and DA-13 (2.43 g, 12.3 mmol) were weighed into a 100 mL four-necked flask equipped with a stirring device, and NMP (49.1 g) was added and stirred to dissolve. DC-3 (7.53 g, 33.6 mmol) was added while stirring the diamine solution, and NMP (30.1 g) was further added, and stirred at 60° C. for 15 hours to obtain a solution of a polyamic acid (A-R1, viscosity: 649 mPa·s, number average molecular weight: 14231).

[0247] <Synthesis Examples 2 to 13>

[0248] The same method as in Synthesis Example 1 was carried out except that the diamine component and the acid dianhydride component were changed as shown in Table 1 below, thereby obtaining polyamic acid solutions (A-R2) to (A-R9) and (A-B1) to (A-B4) shown in Table 1 below. The viscosity and molecular weight of the obtained polyamic acid are also shown in Table 1 below.

[0249] [Table 1]

[0250]

[0251] [Preparation of Liquid Crystal Alignment Agent]

[0252] <Example 1>

[0253] NMP (6.0 g) and BCS (8.0 g) were added to the solution (6.0 g) of the polyamic acid (A-R1) obtained above, and the mixture was stirred at room temperature for 10 hours to obtain a liquid crystal aligning agent (R1) containing 6% by mass of polyamic acid (A-R1), 54% by mass of NMP, and 40% by mass of BCS.

[0254] <Synthesis Examples 2 to 13>

[0255] The same procedure as in Example 1 was carried out except that polyamic acids (A-R2) to (A-R9) and (A-B1) to (A-B4) shown in Table 2 below were used instead of the polyamic acid (A-R1), thereby obtaining liquid crystal aligning agents (R2) to (R9) and (B1) to (B4) of Examples 2 to 13 shown in Table 2, respectively.

[0256] It should be noted that, in Examples 1 to 13 in Table 2, Examples 1 to 3 and 6 to 9 are comparative examples, and Examples 4, 5, and 10 to 13 are examples of the present invention.

[0257] [Table 2]

[0258]

[0259] The solid content ratio in said Table 2 shows the content ratio of the polymer solid content with respect to 100 mass parts of liquid crystal aligning agents, and the solvent composition ratio shows the content ratio (mass part) in each organic solvent.

[0260] <Examples 14~21>

[0261] The liquid crystal aligning agent (R1) obtained in Example 1 and the liquid crystal aligning agent (R4) obtained in Example 4 were mixed in a mass ratio of 3:7, and stirred at room temperature for 3 hours to prepare a liquid crystal aligning agent (B5) of Example 14.

[0262] In addition, in Examples 15 to 21, the liquid crystal aligning agents (B6 to B8, R10 to R13) of Examples 15 to 21 shown in Table 3 below were prepared in the same manner as in Example 14 except that the combinations of the liquid crystal aligning agents used were changed as shown in Table 3 below.

[0263] [Table 3]

[0264]

[0265] <Examples 22~35>

[0266] Liquid crystal alignment films and liquid crystal cells were prepared as described below, and the characteristics of each prepared liquid crystal cell were evaluated. The results are shown in the following Table 4. It should be noted that in the following examples, Examples 22 to 25 and 28 to 31 are embodiments of the present invention, and Examples 26, 27, and 32 to 35 are comparative examples.

[0267] [Production of Liquid Crystal Alignment Film]

[0268] Liquid crystal alignment agents prepared in Examples 1 to 21 were used to prepare liquid crystal alignment films as follows. Each liquid crystal alignment agent was spin-coated on a quartz substrate or a silicon wafer, dried on a hot plate at 70°C for 90 seconds, and then fired in a hot air circulation oven (manufactured by Denko, MB1-1G3030X) at 230°C for 20 minutes to form a liquid crystal alignment film with a film thickness of 100 nm.

[0269] [Measurement of Refractive Index of Liquid Crystal Alignment Film]

[0270] Using a spectroscopic ellipsometer (M-2000 manufactured by JA Woollam), fitting based on the CAUCHY model was performed to measure the refractive index at a wavelength of 250 to 800 nm. The results are shown in Table 4. In Table 4, the refractive index at a wavelength of 550 nm is recorded. The case where the refractive index is greater than 1.62 is defined as "good", and the case where the refractive index is less than 1.62 is defined as "poor".

[0271] [Measurement of Transmittance of Liquid Crystal Alignment Film]

[0272] A measuring box was made using two quartz substrates. A liquid crystal alignment film was formed on one of the two substrates, and the surface on which the liquid crystal alignment film was formed was placed inside, and a quartz substrate without a liquid crystal alignment film was attached. A refractive liquid (contact liquid, manufactured by Shimadzu Equipment Manufacturing Co., Ltd.) was inserted between them using a pipette to make a measuring box. The refractive liquid was used from 11 types with a 0.01 scale from 1.60 to 1.70 according to their respective refractive indices.

[0273] The transmittance of the measurement cell prepared above at a wavelength of 380 to 800 nm was measured using an ultraviolet visible spectrophotometer (UV-2600, manufactured by Shimadzu Corporation). The results are shown in Table 4. Table 4 shows the average value of the transmittance at a wavelength of 380 to 800 nm.

[0274] The case where the transmittance was more than 99.0% was evaluated as "good", and the case where the transmittance was 99.0% or less was evaluated as "poor".

[0275] "Manufacturing of Liquid Crystal Alignment Film and Liquid Crystal Cell"

[0276] Using the liquid crystal alignment agents prepared in the above examples, a liquid crystal cell was fabricated as follows.

[0277] Each liquid crystal alignment agent was spin-coated on the ITO surface of an ITO electrode substrate having an ITO electrode pattern with a pixel size of 100 μm×300 μm and a line width / line spacing of 5 μm, and dried on a hot plate at 70°C for 90 seconds, and then fired in a hot air circulation oven (manufactured by Denko, MB1-1G3030X) at 230°C for 30 minutes to form a liquid crystal alignment film with a film thickness of 100 nm.

[0278] Furthermore, a liquid crystal alignment agent was spin-coated on an ITO surface without an electrode pattern, dried on a 70°C hot plate for 90 seconds, and then fired in a 230°C hot air circulation oven (MB1-1G3030X manufactured by Denko Corporation) for 20 minutes to form a liquid crystal alignment film with a thickness of 100 nm.

[0279] For the two substrates mentioned above, after 4μm bead spacers were spread on the liquid crystal alignment film of one substrate, a sealant (solvent-based thermosetting epoxy resin) was printed from above. Next, the surface of the other substrate on which the liquid crystal alignment film was formed was placed inside, and after being bonded to the previous substrate, the sealant was cured to produce an empty box. Liquid crystal MLC-3023 (trade name manufactured by MERCK) containing a polymerizable compound was injected into the empty box by a reduced pressure injection method to produce a liquid crystal box.

[0280] Then, with a DC voltage of 15 V applied to the liquid crystal cell, 10 J / cm 2 UV that passed through a filter that cuts off wavelengths below 325 nm. It should be noted that the UV illuminance was measured using an ultraviolet irradiance meter (UV-MO3A manufactured by ORC). Then, in order to deactivate the unreacted polymerizable compound remaining in the liquid crystal box, UV (UV lamp: FLR40SUV32 / A-1) was irradiated for 30 minutes using a UV-FL irradiation device (manufactured by Toshiba Lighting & Technology) without applying voltage.

[0281] "Evaluation of LCD Boxes"

[0282] The method for evaluating the characteristics of each liquid crystal cell produced as described above is as follows.

[0283] (Evaluation of vertical orientation)

[0284] The liquid crystal cell was sandwiched between polarizing plates of crossed Nicols and illuminated from behind with backlight, and the liquid crystal cell was rotated to visually observe whether the liquid crystal was vertically aligned by changes in brightness and darkness. The evaluation criteria were as follows.

[0285] ○: The liquid crystal is vertically aligned. ×: The liquid crystal is not vertically aligned.

[0286] [Table 4]

[0287]

[0288] It should be noted that all the contents of the specification, claims, and abstract of Japanese Patent Application No. 2019-173271 filed on September 24, 2019 are cited herein and introduced as a disclosure of the specification of the present invention.

Claims

1. A diamine represented by the following formula (2-1): 2 . A polymer obtained from a diamine component comprising the diamine according to claim 1 . 3 . A polyimide, which is a polyimide precursor obtained by a polycondensation reaction of a diamine component containing the diamine according to claim 1 and a tetracarboxylic acid component, or an imidate of the polyimide precursor.

Citation Information

Patent Citations

  • Liquid crystal display panel and manufacturing method thereof

    JP2008076950A

  • Sanitary washing apparatus

    JP2019173271A

  • Liquid crystal display device and polymer for aligning film material

    WO2008117615A1

  • Liquid crystal orienting agent, liquid crystal display element, and method for producing liquid crystal display element

    WO2016125870A1